Surface effects on the degradation mechanism of bioactive PDMS-SiO2-CaO-P2O5 hybrid materials intended for bone regeneration. Issue 1 (January 2017) - Sánchez-Téllez, D.A.; Téllez-Jurado, L.; Rodríguez-Lorenzo, L.M.; Mazo, M.A.; Rubio, J.; Tamayo, A.
Abstract: The purpose of this work is to study the dissolution mechanism of SiO2 -based bioactive hybrid materials containing both CaO and P2 O5 in their structures and to determine the influence of apatite crystallization over the surface features of the hybrids during degradation. Hybrid materials were synthesized using sol–gel method. Tetraethoxysilane (TEOS), hydroxyl terminated polydimethylsiloxane (PDMS), Ca(NO3 )2 ·4H2 O, and triethyl phosphate (TEP) were used as reactants. The degradation and bioactivity of the hybrid materials were tested by soaking the specimens into simulated body fluid (SBF). Raman spectroscopy, tensiometry and N2 adsorption/desorption curves were used to measure the changes during the degradation experiments. Several mathematical approaches have been taken to analyze the results. The growth of an apatite layer on the surface of SiO2 -modified PDMS-P2 O5 -CaO hybrid materials occurs together with degradation of the silica-based matrix. The dissolution kinetics depends upon the composition of the material. It varies from a surface-driven mechanism in the case of low-P2 O5 samples to a degradation path which fits into a Weibull type kinetic model, typical of matrix dissolution processes in materials enriched in P2 O5 . During degradation, the surface parameters, fractal constant and anisotropy of the pores were determined. The slight increase of the fractal constant in low-containing P2 O5 materials suggests the formation of a homogeneous silica-like layer in the first stage of degradation, which also works as anchoring nucleus for subsequent apatite formation. In all the cases, the degradation leads to ink-bottle shaped pores, increasing their volume as degradation occurs, but keeping their neck shape. Graphical abstract: